A demanda por serviços privados de saúde: uma análise por episódios para o caso Sabesprev - Daniela Goes Paraiso (2005)
The aim of this study is to investigate the determinants of the demand for health services among a population that had private insurance. We used data from the Fundação Sabesp de Seguridade Social (SABESPREV), in order to examine the behavior of different categories of episodes (chronic, acute inpatient, outpatient and obstetric) according with the main socioeconomic and demographic characteristics of the individual. We used the Tobit model to analyze the expenditure decision and the conditional mean value. The main results of this work indicate that the sex and age variables are important in the determination of all health care episodes. In general, we observe that children, women in the reproductive age period and the elderly population have a higher probability of using health services, as well as conditional expenditure. The variables income and years of schooling determine the demand for clinic and preventive services. The past heath status is relevant to analyze chronic disease episodes is represented by several proxies which attempt to inform about the individual health status. The results of the estimate are important for the discussion of how to reduce the inequalities in health services, once that the estimated coefficient shows that there are important differences among age groups and sex in the demand for health services.